Strength training variables: an integrative review (Research, Society and Development, 2021)
Strength training is a training modality well known in Brazil and in the world, due to the simplicity in the execution of movements and mainly to the several benefits that are provided. Benefits for some organs and systems in the human body, such as the heart, brain, blood vessels and, of course, for skeletal muscle system. However, to obtain these benefits, the prescription of strength training needs to be individualized and adopt some criteria to achieve the practitioner's goals. Within these criteria, there are many variables that need to be understood and applied in the exercise prescription. Thus, the objective of this review is to analyze the use and conceptualization of strength training variables, as well as to elucidate these issues for a better training prescription.